Desorption Equilibrium Moisture Content Isotherm of Corn - Lamhot P. Manalu (Jurnal Keteknikan Pertanian, 2001)
The concept of equilibrium moisture content or EMC is important in study of storage. The EMC of cereal grain is defined as the moisture content' of the material after it has been exposed to a particular environment for an infinitely longperiod of time. The EMC is dependent upon the humidity and temperature conditions of the environment.The more important limitation in process design for agricultural products is the lack of exprimental data can be found. The variety of products and the differences in measurement method make limitation on the valueof the available data, especially for Indonesian's products. The data are needed to get information about moisture content change when product was processed like storage or drying.The objective of this research is to determine the EMC equation models of local corn with the static method. The result indicates that Chung-Pfost and polynomial models are better reprentative to predict the EMC than Henderson's.